Study on the character of chitinase produced by Trichoderma spp. with measuring reducing sugar - LIU Kai-qi; XIANG Mei-mei; LIU Ren; ZENG Yong-san; LI Hua; JIANG Xin-yin; ZHANG Yue-li (浙江大学学报. 农业与生命科学版)
A trusty and intuitionistic method for screening chitinase produced by Trichoderma spp. was developed. 38 isolates of Trichoderma spp. were cultured in liquid medium with chitin or colloidal chitin as the sole carbon source for 4 days. The supernatant of the fermented broth was mixed with colloidal chitin and heated in water-bath at 37 ℃ for 30 min, then 3,5-dinitrosalicylic acid reagent (DNS) was added to the mixture, and let them react for 10 min in water-bath. According to the different colour of the mixture, the isolates of Trichoderma spp. which can produce chitinase could be screened.